Teknik Budidaya Lele Dumbo (Clarias gariepinus) dengan Sistem Booster - Putri Nurhanida Rizky; Daniel Bona Simamora; Moh. Zainal Arifin; Nazran Nazran (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2024)
Booster system fish farming has been widely used by cultivators since 2014. Booster system farming is a way of cultivating fish by emphasizing water, feed and health management applications to reduce the risk of crop failure. This study aimed to examine the production performance and cultivation techniques of African catfish with a booster system on an industrial scale, without experimental design. Feed management in this cultivation system is carried out by adding grotop boosters, aquavita premix boosters and progol boosters in 1 kg of feed. The average weight of African catfish when stocking was 6.03 ± 0.06 g/fish with a density of 2,025 in 4 concrete pond units. This studies showed after 77 days of culture, the highest fish weight gain was in pond T4 of 80.17 ± 0.56 g/fish, followed by T2 of 79.94 ± 0.97 gr/fish, T1 of 78.92 ± 0 .91 gr/fish, and T3 of 78.27 ± 0.33 gr/fish. The survival rate in this study was also high where the survival rate was >90% with an FCR value of 1.2.